CHANGE MANAGEMENT IN INSTITUTIONS OF HIGHER EDUCATION IN ACHIEVING THEIR COMPETITIVENESS - Verbovska , L. S. (The actual problems of regional economy development, 2023)
The article examines the issue of change management in higher education institutions in modern conditions. The relevance of the research is timely, because change management forms the tools and basis for the formation of competitive goals in the conditions of changes in the external environment, which is dictated and determined by modern trends of competitive advantages of higher education institutions; partnership cooperation with stakeholders; increasing the competitiveness of scientific and pedagogical personnel; diversification of new areas of scientific activity and new opportunities for university development. In the process of writing a scientific article, various general scientific research methods were used. The conducted analysis showed that the most important component in determining competitive advantages is primarily the improvement of the quality of education and the positioning of higher educational institutions as a competitive business entity on the market of educational services, capable of forming a competitive specialist adapted to market conditions who will work at the international level, analysis of the provision of educational services consumers. The system for ensuring the process of implementation of changes has been improved.Indicators of implementation of changes include: organizational; economic; managerial and strategic. The international internships of the scientific and pedagogical staff of the University for the specified period were analyzed. The description of the Center as a competitive tool of the University, namely the "Center for the Advancement of Qualifications of the NPP IFNTUNG", which is capable of providing high-quality services, was carried out. It has been proven that higher education institutions should form a high-level international reputation, diversify international research and publications; to be a participant and/or main partner in grant programs; to present university projects on international platforms, etc. The practical value of the study lies in the analysis of the factors of international competitiveness of higher education institutions; a description of the concepts of key factors in the formation of a world-class university.